The Development of Digital Pocket Book Learning Media Animation Based On Science Subjects at SMP Negeri 3 Telaga, Gorontalo District - Paramata, Dewi Diana; Uloli, Ritin; Musa, Ronal (Universitas Muhammadiyah Sidoarjo, 2025)
This research aims to develop digital pocket book learning media based on animation on circulatory system material, as well as describing the suitability of the media in terms of validity, practicality and effectiveness. This research method uses Research and Development (R&D) research according to Brog and Hall. In this research, it was carried out in a limited trial, the subjects for the trial were 22 students in class VIII of SMP Negeri 3 Telaga. The results of this research are: 1) Validity of learning media which consists of validation of material experts and media experts. Material expert validation consisting of 83% introductory aspects, 96% learning material, and 100% conclusion with very feasible criteria. Meanwhile, the validity of media experts with assessment aspects consisting of 100% application introduction, 100% appearance, 88% end of application, and 100% linguistics obtained the criteria, namely very feasible. 2) Practicality is seen from the implementation of teacher and student activities. The implementation results at the first meeting obtained a percentage of 100% with very good criteria, at the second meeting they obtained 89% -100% with very good criteria. Meanwhile, students' activities at the first meeting obtained a percentage score of 67% -89% with good and very good criteria, at the second meeting they obtained 78% -89% with good and very good criteria. 3) Effectiveness in terms of student learning outcomes obtained a total n-gain of 15.80 with an average n-gain of 0.72 obtaining high criteria.